Exploring factors associated with obesity in Argentinian children using structural equation modeling - Ignacio Mendez; María Victoria Fasano; Alicia B. Orden (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2023)
Abstract: Habits and behaviors related to obesity risk are strongly associated with the family environment and are affected by socioeconomic factors. Structural equation modeling (SEM) allows us to hypothesize on how the relationships between these factors occur and measure their impact. This study aimed to explore the relationship between family socioeconomic indicators and childhood obesity, mediated by habits linked to energy balance, applying a SEM. A cross sectional study was performed on 861 Argentinian schoolchildren aged 6-12 years, from 2015 to 2016. The model included three latent variables: socioeconomic status, healthy habits, and obesity. Socioeconomic status indicators and healthy habits were surveyed by self-administered parental questionnaires, whereas obesity indicators were evaluated with anthropometry. The applied model showed an acceptable fit (NFI = 0.966; CFI = 0.979; RMSEA = 0.048). Socioeconomic status positively influenced parental education, health insurance, and car possession, while negatively influenced crowding (p < 0.001). Healthy habits significantly influenced physical activity, meals frequency, and sleep hours, while negatively influenced sedentary hours and mother's nutritional status (p < 0.001). Obesity factor positively influenced body mass index, body fat, and waist-to-height ratio (p < 0.001). Finally, socioeconomic status positively influenced health habits, which in turn negatively influenced obesity factor. Healthy habits (especially physical activity and mother's nutritional status) mediated the relationship between socioeconomic status and child obesity. Further research should include other indicators related to diet, eating habits, and physical activity like neighborhood characteristics.